Alternatif Penjatuhan Pidana sebagai Upaya Pencegahan Faktor Kriminogen - G Aryadi (Jurnal Hukum IUS QUIA IUSTUM, 2002)
This article is focussed on penal sentencing which can become a crime causing factor. Too much depending on the criminal law is not realistic bcause its capacity is limited. Some altenatives, the refore shouldbe developed in order to prevent the crime causing factor resulted from penal sentencing such as avoiding criminal justice process, and selective and limilative implementation of criminal law, meaning to say that it can be implemented only aftet other social means are not effective anymore to overcome of fences.